MICROBIAL EXAMINATION OF DIFFERENT COOKED RICE SOLD AT DIFFERENT RESTAURANTS IN UNIVERSITY OF MAIDUGURI - AUTA, ALI AMINA; DIRAM, FATIMA UMAR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
This study focused on examination of rice served in university of Maiduguri restaurants for microorganisms. Three different rice samples which include fried rice, jollof rice and white rice were collected aseptically from different restaurants in University of Maiduguri campus. Different media which include MacConkay agar, Nutrient agar, Malt extract agar, Sabouraud dextrose agar, Corn meal agar, Lacto phenol cotton blue was prepared and used for culturing the organisms. After the culturing of the organisms macroscopic, microscopic and biochemical tests were used for the isolation and identification of the organisms. Three types of bacteria and fungi were identified. The bacteria isolated includeStaphylococcus aureus from the fried rice, Escherichia coli isolated from Jollof rice and Klebsiella pneumonia were isolated from white rice with average load of 2.0x105, 5.0 x 107 and 2.0x 107respectively. While the fungi isolated from fried rice was Aspergillus niger, Aspergillus flavus from jollof rice and Fusarium species from white rice with average load of 3.0 X 105, 6.8 X 107, 3.4 X 107cfu/g. This report showed that ready-to-eat food samplesdid not meet the bacteriological quality standard. The presence of pathogenic bacteria in ready-to-eat foods should receive particular attention, because their presence indicates public health hazard and give warning signal for the possible occurrence of foodborne poisoning More closely supervision should be made on these restaurants around the University of Maiduguri by relevant authorities, and more analysis should be carried out on other food samples sold in the University of Maiduguri environment, to ensure proper food quality and safety standards.